2004
DOI: 10.1016/j.prehos.2004.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A paramedic-staffed medical rehydration unit at a mass gathering

Abstract: This article defines a new role for paramedics and describes the operation of a medical rehydration unit at a large, single-day mass gathering in summer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…‘Just under half’ of treated patients remained in the community and others were admitted by ‘the most appropriate pathway’, generating an estimated saving of £28 279 per annum (compared with routine GP and EMS care). Paramedics trained to assess and manage heat-injury patients at a mass event (450 000people) in urban Canada managed 126 patients who would have otherwise burdened another site care facility 25. Evaluations by the same author team of screening by paramedics initially focused on patients aged over 6526 but later those over 6027 which makes interpretation in relation to older patients difficult.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…‘Just under half’ of treated patients remained in the community and others were admitted by ‘the most appropriate pathway’, generating an estimated saving of £28 279 per annum (compared with routine GP and EMS care). Paramedics trained to assess and manage heat-injury patients at a mass event (450 000people) in urban Canada managed 126 patients who would have otherwise burdened another site care facility 25. Evaluations by the same author team of screening by paramedics initially focused on patients aged over 6526 but later those over 6027 which makes interpretation in relation to older patients difficult.…”
Section: Resultsmentioning
confidence: 99%
“…This review identified four ‘good’,1 19 25 34 eight ‘moderate’5 8 10 23 24 27 28 30 and two ‘poor’ quality articles 15 25. All studies, except one,35 address a clearly focused question using an adequate, if not always ideal methodology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been no published studies on the impact of WYD events on hospitals, although prehospital care 3 and systems for syndromic surveillance 4 have been examined. Compared with other pilgrimages, WYD is unusual in that the pilgrimage is not to a holy site, as with the Hajj, whose health implications (eg, heatstroke, infection) have been well described 5 , 6 .…”
Section: Year City Country Final Papal Mass Attendancementioning
confidence: 99%